2014
DOI: 10.1371/journal.pone.0098383
|View full text |Cite
|
Sign up to set email alerts
|

Snx14 Regulates Neuronal Excitability, Promotes Synaptic Transmission, and Is Imprinted in the Brain of Mice

Abstract: Genomic imprinting describes an epigenetic process through which genes can be expressed in a parent-of-origin-specific manner. The monoallelic expression of imprinted genes renders them particularly susceptible to disease causing mutations. A large proportion of imprinted genes are expressed in the brain, but little is known about their functions. Indeed, it has proven difficult to identify cell type-specific imprinted genes due to the heterogeneity of cell types within the brain. Here we used laser capture mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…SNX14 has been isolated from mouse embryonic stem cell (ESC)-derived neurons and was found to be expressed at high levels in the nervous system (Carroll et al, 2001). A recent study has found that SNX14 protein levels are progressively increased during neuronal development, whereas its knockdown severely impairs both excitatory and inhibitory synaptic transmission (Huang et al, 2014). Another study has found that SNX14 mutations cause a distinctive autosomal-recessive cerebellar ataxia and intellectual disability syndrome (Thomas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SNX14 has been isolated from mouse embryonic stem cell (ESC)-derived neurons and was found to be expressed at high levels in the nervous system (Carroll et al, 2001). A recent study has found that SNX14 protein levels are progressively increased during neuronal development, whereas its knockdown severely impairs both excitatory and inhibitory synaptic transmission (Huang et al, 2014). Another study has found that SNX14 mutations cause a distinctive autosomal-recessive cerebellar ataxia and intellectual disability syndrome (Thomas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the pattern the cerebellum is the region where SNX14 is most highly expressed and transcript levels continue to increase through postnatal life until adult (UKBEC data, Figure S6). Most recently, Huang et al 36 described mouse SNX14 levels as being high in brain, testis, and lung, similarly showing an increase in cerebellar levels from embryonic to postnatal stages (E16.5-p63). Despite a broadly distributed spatiotemporal pattern, which might suggest function in many tissues, high levels in the central nervous system and particularly cerebellum correspond to the described phenotype (with internal organs spared), particularly the cerebellar atrophy seen in affected individuals from all three families presented here.…”
mentioning
confidence: 99%
“…Snx14 knockdown studies using lentiviral shRNA, specifically in mouse cortical pyramidal neurons, were recently reported. 36 Despite incomplete (60%) knockdown, significantly reduced intrinsic excitability and synaptic function was recorded. The study of Huang et al 36 also reported Snx14 to be maternally imprinted but suggest that this might be mouse specific.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its increased expression in the temporal cortex has also been correlated with temporal lobe epilepsy, although its direct role in the disease has not been confirmed (18). The SNX14 protein is expressed in motor neurons (19) and recent studies suggest that the Snx14 gene is paternally imprinted in neuronal cells, where it promotes synaptic transmission through unknown mechanisms (20). SNX19 is the only member of the family lacking an RGS domain (see below).…”
mentioning
confidence: 99%